Implementasi Wireless Router dengan Menggunakan Raspberry Pi 3 - Hartono Jefton; Justinus Andjarwirawan; Agustinus Noertjahyana (Jurnal Infra, 2017)
At this time, the router becomes one of the important needs. Most users use a common router on the market, and the router can only be functional as a router, in the financial side it's certainly not profitable.Based on background of the problem, then Implementation of Wireless Router by Using Raspberry Pi 3 which is a small multifunctional computer that can be use to run OpenWRT operating system and it can use I2C 16x2 LCD which can display brief information of network that is running.Results that had been obtained from trials that have been made, are able to make Raspberry Pi 3 into a router with security systems and able to display bandwidth and number of clients on LCD I2C 16x2.